Reasons of State Oil Politics and the Capacities of American Government - Ikenberry, G. John (Cornell University Press, 2018)
In this lucid and theoretically sophisticated book, G. John Ikenberry focuses on the oil price shocks of 1973-74 and 1979, which placed extraordinary new burdens on governments worldwide and particularly on that of the United States. Reasons of State examines the response of the United States to these and other challenges and identifies both the capacities of the American state to deal with rapid international political and economic change and the limitations that constrain national policy.